Evaluation of serum brain-derived neurotrophic factor, IL-6, IL-10, and TNF-a cognitive function, and sleep quality in elderly patients with major depressive disorder and somatic symptoms - Gao Ya; Liu Xu; Gu Yan (Journal of Medical Biochemistry)
Background: The aim of the paper was to analyze the relationship between somatization in elderly patients with major depressive disorder (MDD) and brain-derived neurotrophic factor (BDNF), IL-6, IL-10, and TNF-a cognitive function, and sleep quality (SQ). Methods: This was a case-control study on 80 elderly patients with MDD who were grouped based on the somatic self-rating scale (SSS) - the subjects with somatic symptoms (SS) as the AG and the subjects without SS as the BG. Additionally, 25 healthy volunteers from the same period were included as the control group (CG). The subjects' SQ scores, BDNF and its precursor (ProBDNF), and cognitive function scores were collected. Results: The SQ and SS scores of AG and BG were visibly higher than against CG, and those of AG were visibly higher in contrast to BG. The cognitive function scores of AG and BG were visibly lower than against CG, and the score of AG was lower than BG (P<0.05). There was a similarity in BDNF and ProBDNF levels between AG and BG (P>0.05). CRP, IL-6, IL-10, and TNF-a in both AG and BG were visibly higher as against CG; Those were visibly higher in AG as against BG (P<0.05). The SS scores of the patients suggested a visible negative correlation with cognitive function scores and an evident positive correlation with SQ scores. Conclusions: Somatization symptoms may affect the SQ and cognitive function of people with depression, leading to an exacerbation of inflammatory responses; BDNF and ProBDNF levels may be more influenced by the overall state of depression rather than being determined solely by SS.